STUDENTS' ENGLISH INTONATION ABILITY IN USE: A STUDY OF FOURTH SEMESTER ENGLISH DEPARTMENT STUDENTS AT IAIN PAREPARE - Basmala Basmala; Abdul Haris Sunubi; Kalsum Kalsum (Journal of English Education, 2025)
This study examines the proficiency level of fourth-semester EFL students at IAIN Parepare regarding their application of English intonation patterns. Intonation serves as a crucial element within pronunciation that significantly influences meaning conveyance and emotional expression during verbal communication. The research employed a quantitative descriptive approach involving twenty student participants. Data collection utilized two assessment instruments: a multiple-choice examination and voice recording tasks, each containing ten items focused on ascending and descending intonation patterns. Research findings indicate that students demonstrate "Fair" competency in English intonation usage, achieving mean scores of 58.5 on the multiple-choice assessment and 59.5 on the voice recording evaluation. Data analysis reveals that most participants encounter difficulties implementing descending intonation patterns, particularly at sentence-final positions. Contributing factors to these challenges include native language interference and habitual use of elevated pitch during daily communication, especially among students from Buginese cultural backgrounds. These research outcomes provide concrete insights into areas requiring enhanced emphasis within pronunciation instruction, specifically intonation components, to improve students' communicative effectiveness in English.